Fair food futures UK: Protocol for a mixed methods study exploring what approaches adopted by community food organisations are more likely to prevent the need for emergency food in two multicultural communities in Northern and Southern England - Laura Sheard; Giorgia Previdoli; Wendy Burton; Rachel Benchekroun; Maddy Power; Bob Doherty; Philip Hadley; Ariadne Beatrice Kapetenaki; Shahid Islam; Sairah Mirza; Claire Cameron; Kate Pickett; et al. (PLoS ONE, 2025)
Introduction Food insecurity reduces people’s chances to live healthy and active lives and places a significant burden on healthcare systems. Levels have significantly increased in the UK since 2010, due to the impact of austerity and, more recently, the COVID-19 pandemic and the cost of living crisis. This increase is projected to continue. Households with children are amongst those at highest risk for food insecurity. A variety of community food organisations (CFOs), such as community gardens, community kitchens, food banks and social markets, have been essential in responding to rising food insecurity, including providing emergency food and other types of support such as welfare advice. However, beyond food banks, little is known about differing approaches to food aid in the UK, including how these organisations provide additional services to address the underlying issue that has led someone to seek emergency food support. Aim To understand what approaches used by community food organisations are most likely to help prevent the need for emergency food in two multicultural communities in the North (Bradford) and South (Tower Hamlets, London) of England, with high levels of ill-health and food insecurity. Research design, setting and participants This is a mixed methods study informed by complex systems theory. Methods include participatory systems mapping and qualitative longitudinal research. We will map the availability and type of help with food, and produce a typology of CFO approaches, using a survey, multiple local and national participatory system mapping workshops and interviews with local and national stakeholders (WP1). Then, we will conduct a longitudinal qualitative research using a ‘researcher in residence’ approach in up to 10 CFOs purposively sampled to reflect the diversity of prevention strategies adopted by CFOs. Research will include: a) a 12 month ethnographic study; b) three waves of ‘go along’ interviews with up to 35 families; and c) a visual study where the same families are invited to share photos and videos about their food thoughts via Indeemo research app. Outputs and dissemination Outputs will include: a) a toolkit on CFOs to support local and national policy and implementation decisions, b) a travelling exhibition with visual representations of people’s lived experiences c) publications in academic journals, d) blog posts, e) public talks, and f) policy briefs. Findings will help decision makers to invest in the most accessible, beneficial and culturally appropriate resources for communities.